Analysis Health Reproductive Knowledge Toward Attitude Premenstrual Syndrome In Adolescent - Agnes Erida Wijayanti; Yustinus Wahyu (Jurnal Keperawatan Respati Yogyakarta, 2020)
Knowledge of adolescents in Indonesia about reproductive health is still very low. For example menstruation as the puberty of women. Boys who know menstruation are around 37% (20-24 years) and 32% (15-19 years). While girls around 78% (20-24 years) and 75% (15-19 years). The research method used was a non-experimental study with a cross-sectional design. The population in this study were junior high school students, who had menstruated as many as 46 children. The sampling technique uses purposive sampling where the researcher determines the sampling by determining the special characteristics of the randomly chosen sample selection that has been menstruating by the Guidance Counseling teacher that are class VII and VIII then analyzing the data using the Spearman Rank test. The results of the study using the Spearman rank test showed a significance of 0,000 (p = 0,000 <0.01) so that there is a relationship between reproductive health knowledge with attitudes toward premenstrual syndrome in adolescents at Prambanan junior High School.